2001
DOI: 10.1159/000047638
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Hemorrhage and Oral Anticoagulant Treatment

Abstract: Objective: To detect risk factors for intracranial hemorrhage (ICH) in patients with long-term oral anticoagulant and to identify clinical or radiological data specific of anticoagulant-related ICH. Methods and Patients: Three groups of patients were included. Group 1 represents patients who were admitted because of anticoagulant-related ICH between January 1984 and February 1996. All patients underwent CT scan. Clinical data, anticoagulation parameters, location and volume of the ICH, treatment and the 30-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 29 publications
3
38
0
3
Order By: Relevance
“…In the 15 of these patients who also received PCC, the dose of FFP was 1-2 units, as specified by the protocol (when given with PCC). However, in the remaining patients (FFP and vitamin K alone), doses of FFP were also small (median 2 units, range [1][2][3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…In the 15 of these patients who also received PCC, the dose of FFP was 1-2 units, as specified by the protocol (when given with PCC). However, in the remaining patients (FFP and vitamin K alone), doses of FFP were also small (median 2 units, range [1][2][3][4][5][6].…”
Section: Resultsmentioning
confidence: 99%
“…A statistical analysis of aggregated data from previous studies shows that mortality in AC-related ICH is, on average, 14% units higher (range 10% to 32% units) than in spontaneous ICH [3][4][5]8 (PϽ0.01). Although it was not the main aim of the present study, we could verify this observation in a subset of our patients because a comparison could be made with a previously published patient material of spontaneous ICH from 1 hospital.…”
Section: Discussionmentioning
confidence: 97%
“…Compared with spontaneously occurring ICHs, AC-related ICHs are often larger and carry a higher mortality (44% to 68% at 1 to 6 months). [3][4][5][6][7][8] Low prothrombin complex values, ie, high international normalized ratios (INRs), increase the risk of ICH, 8,9 but the relationship between the INR value on admission and the prognosis has not been extensively studied. 3,10 Major textbooks published in the early 1990s and a recently published authorized guideline provide either no specific recommendations of pharmacological treatment of AC-related ICH in the acute phase, 11,12 or they recommend the use of vitamin K or plasma.…”
mentioning
confidence: 99%
“…15 Nevertheless, most warfarin-associated ICH cases occur during times when warfarin is in the therapeutic range (international normalized ratio [INR] 2.0-3.0). 16,17 Dabigatran, an oral direct thrombin inhibitor, has recently been approved by the Food and Drug Administration ( [FDA] October 2010) 18 for the prevention of stroke and blood clots in patients with abnormal heart rhythm (atrial fibrillation). In a randomized trial (dabigatran vs warfarin in patients with atrial fibrillation, RELY), [19][20][21] it was found that dabigatran was not inferior to adjusted dose warfarin for the prevention of cardioembolic stroke in the setting of atrial fibrillation, and it had less major bleeding complications than warfarin.…”
Section: Introductionmentioning
confidence: 99%